Chaos in the contact zone : unpredictability, improvisation and the struggle for control in cultural encounters - Behrens, Christoph, 1962-; Wodianka, Stephanie, 1971- (Culture & theory., 2017)
Cultural encounters are often being stylized not only as experiences of uncontrollability and unpredictability par excellence, but also as challenges to planning and predicting. The history, the different forms and the consequences of this phenomenon are the main issues discussed in this volume. The contributions show that chaos and control are not mutually exclusive in the "contact zone" (Mary Louise Pratt); on the contrary, they stand in relation to each other - be it as a competence or as an interpretive scheme.